Azospirillum ramasamyi sp. nov., a novel diazotrophic bacterium isolated from fermented bovine products. Issue 5 (27th February 2019) - Anandham, Rangasamy; Heo, Jun; Krishnamoorthy, Ramasamy; SenthilKumar, Murugaiyan; Gopal, Nellaiappan Olgaganathan; Kim, Soo-Jin; Kwon, Soon-Wo
Abstract : A Gram-stain-negative, rod-shaped, aerobic bacterium, designated M2T2B2 T, was isolated from fermented bovine products in Suwon, Republic of Korea. The strain displayed growth at 15–45 °C (optimum, 28–30 °C), pH 6.0–10.0 (pH 7.0) and 0–2 % (w/v) NaCl (0 %). Colonies were light pink-coloured, round and convex. The cells were positive for oxidase and weakly positive for catalase. The major fatty acids in whole cells of strain M2T2B2 T were summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ), followed by summed feature 3 (C16 : 1 ω 7 c /C16 : 1 ω 6 c ), summed feature 2 (C12 : 0 aldehyde/unidentified 10.928/C14 : 0 3-OH/iso-C16 : 1 I), C16 : 0, C18 : 1 2-OH, C16 : 0 3-OH and C17 : 1 ω 6 c . The polar lipids were phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylcholine, phosphatidylglycerol, and three unidentified aminolipids. Ubiquinone 10 was the predominant ubiquinone. The DNA G+C content was 68.0 mol%. The strain could fix atmospheric nitrogen, which was evaluated by the acetylene reduction assay. Further, whole genome sequence analysis revealed the presence of a nif gene cluster. Strain M2T2B2 T showed the highest 16S rRNA, rpoD and nifH gene sequence similarity to members of the genus Azospirillum, and showed 97.6 % 16S rRNA gene sequence similarity to Azospirillum oryzae COC8 T . The phenotypic, phylogenetic and genomic analyses support the proposal of strain M2T2B2 T as being a novel species of the genus Azospirillum, for which the name Azospirillum ramasamyi sp. nov. is proposed. The type strain is M2T2B2 T (=KACC 14063 T =NBRC 106460 T ).